PENDIDIKAN MORAL PADA LINGKUNGAN KELUARGA UNTUK MENGATASI KENAKALAN REMAJA PADA MASA MENDATANG - Noviansah, Ahmad; Maemunah, Maemunah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
In order for children to have good moral and avoid violations of moral transgression, there needs to be coaching early moral value to the children in the family. The family environment is a place where children are raised and are the first to live by a child in their life, so that what the children see and feel in the family will be able to influence the growth and development of a child’s soul. In order for the child to have good moral then the first step we must keep to our children has so that the children have strong faith. The process of building the values of the faith to be implanted to children can be started from birth to adulthood. When born is introduced a good sentence or can we say the sentence Toyibah, then after they grow and develop into children, then the first we must do is the values of religion related to the faith so that the child believes in the presence of God and can know God with his confidence. Along with that, children are guided by the moral value itself such as a good-spoken way of good dress, such as the values of honesty you eat a simple live koi fish, patience and others. Moreover, in order that children have good moral values also in the family, especially between mother and father must maintain the harmony of relations between the two is to be a example and his children.